2016
DOI: 10.1111/soc4.12395
|View full text |Cite
|
Sign up to set email alerts
|

Racial Identity Contestation: Mapping and Measuring Racial Boundaries

Abstract: Survey based research typically uses a single measure of racial self‐classification to study racial inequality and to make group based comparisons. Race, however, is multidimensional; experienced not only in accord with how one self‐identifies, but also in relation to how one is perceived racially by others. For example, an individual can self‐identify racially as Black, but be perceived by most others as non‐Black. We refer to this experience as racial identity contestation. We briefly review the growing set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 67 publications
2
20
0
Order By: Relevance
“…It is important to point out that differences by phenotype are distinct from differences between internal (subjective self-identification) and observed (the race others assume you to be) R/E (Roth, 2010; Vargas & Kingsbury, 2016). Racial identity contestation refers to when one identifies as one R/E but is perceived by most others as a different R/E.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to point out that differences by phenotype are distinct from differences between internal (subjective self-identification) and observed (the race others assume you to be) R/E (Roth, 2010; Vargas & Kingsbury, 2016). Racial identity contestation refers to when one identifies as one R/E but is perceived by most others as a different R/E.…”
Section: Resultsmentioning
confidence: 99%
“…), then having data on how others perceive a person rather than self-identification can correlate better with inequality measures. Vargas and Kingsbury (2016:719) wrote a critical review on “racial identity contestation” or “the discordance between racial identity and racial identification given the racial categories available” and how understanding racial identity contestation is useful for understanding ongoing racial projects and implications for studying racial inequality. Saperstein (2012) found that income and health care correlate with two measures of racial identity: how a person self-identifies and an assigned identity by an interviewer.…”
Section: Issues With Collecting Racial and Ethnic Demographicsmentioning
confidence: 99%
“…Other work has begun to question the subjective and cultural adequacy of fixed racial and ethnic classifications (Boehmer et al 2002;Brown, Hitlin, and Elder 2006;Harris and Sim 2002;Roth 2016;Saperstein 2012Saperstein , 2013Saperstein and Penner 2012). Studies have found significant variation between how researchers perceive and classify their subjects' race and the self-identified racial identities of those subjects (Boehmer et al 2002;Brown et al 2006;Harris and Sim 2002;Roth 2016;Vargas and Kingsbury 2016;Vargas and Stainback 2016). A given individual's racial identity can shift over time as well (Saperstein 2012(Saperstein , 2013Saperstein and Penner 2012).…”
Section: Changing and Fluid Racial Identities?mentioning
confidence: 99%